Modification of Nitrate Ion Enables Stable Solid Electrolyte Interphase in Lithium Metal Batteries - Hou, Li‐Peng; Yao, Nan; Xie, Jin; Shi, Peng; Sun, Shu‐Yu; Jin, Cheng‐Bin; Chen, Cheng‐Meng; Liu, Quan‐Bing; Li, Bo‐Quan; Zhang, Xue‐Qiang; Zhang, Qiang (Angewandte Chemie International Edition, 2022)
The lifespan of high‐energy‐density lithium metal batteries (LMBs) is hindered by heterogeneous solid electrolyte interphase (SEI). The rational design of electrolytes is strongly considered to obtain uniform SEI in working batteries. Herein, a modification of nitrate ion (NO3−) is proposed and validated to improve the homogeneity of the SEI in practical LMBs. NO3− is connected to an ether‐based moiety to form isosorbide dinitrate (ISDN) to break the resonance structure of NO3− and improve the reducibility. The decomposition of non‐resonant −NO3 in ISDN enriches SEI with abundant LiNxOy and induces uniform lithium deposition. Lithium–sulfur batteries with ISDN additives deliver a capacity retention of 83.7 % for 100 cycles compared with rapid decay with LiNO3 after 55 cycles. Moreover, lithium–sulfur pouch cells with ISDN additives provide a specific energy of 319 Wh kg−1 and undergo 20 cycles. This work provides a realistic reference in designing additives to modify the SEI for stabilizing LMBs. The modification of NO3− is achieved by connecting NO3− to an ether‐based moiety. The broken resonance structure of −NO3 improves its reducibility compared with NO3−. The decomposition of −NO3 forms a LiNxOy‐rich solid electrolyte interphase (SEI) and induces uniform Li deposition.